The Impact of Creative Contexts: An Application Cases Review - Sergio Degiacomi Garbero; Chiara Lorenza Remondino; Paolo Tamborrini (DIID)

(untitled)
The article delves into the multifaceted nature of creativity, moving beyond traditional associations of creativity with artistic or cultural disciplines. Instead, it presents creativity as a complex cognitive process essential for addressing multidisciplinary challenges. Drawing from various studies, it emphasises how creativity flourishes in sociocultural contexts and is shaped by both individual learning and group dynamics, such as those described by Florida’s concept of the Creative Class. The dissertation’s core focuses on exploring various creative contexts and environments that nurture creativity. The methodology considers a Systemic Innovation Design perspective to analyse thirty application cases of creative spaces, identifying key characteristics and impacts. The results show a clear direction of creative contexts involving multidisciplinary and practice-based actions, with a predominant focus on social and applied sciences.